Financial contribution of taxes on Foreign oil companies in support of the state budget: The case of a foreign oil company in the Iraq Study (Journal of Accounting and Financial Studies ( JAFS ), 2019)
Imposed on foreign oil companies from important sources in the financing of the general budget in most countries of the world income tax is considered as well as be used to achieve political, economic and social goals, and has developed the concept of the tax until it became play an important role in influencing the economic conditions of a country, and the aim of this research is to statement imposed on foreign oil companies operating in Iraq in the financing of the state budget income tax contribution, as well as clarify the contracts type contracts with these companies, which is in favor of Iraq, together with the Income Tax Law No. (19) for the year / 2010, and instructed No. (5) for the year / 2011, which organized the tax process settling accounts with these companies. The research has come to the most important set of conclusions.1.That contracts with foreign oil companies contracting for work in Iraq has created a new resource for the general budget of the state by imposing taxes and fees on the income of these companies, which provide sufficient funding sources to cover the overhead of the State.2.Iraq is one of the oil countries, which occupies a leading position among Arab and international oil-producing countries of the magnitude of the reserves position of the oil sector is one of the most important pillars of the Iraqi economy to being an important source of attracting foreign to work in Iraq, the oil companies, which contribute to the development and reconstruction of the national economy, with the introduction of modern technologies in the the oil industry.3.The income tax on foreign oil companies contracting for work in Iraq Law No. (19) for the year 2010 and instructed No. (5)- for the year 2011 began for the purpose of supporting the national economy and the submission of income earned in Iraq to foreign oil companies and its sub-contractors in the production and extraction of oil and gas income tax.Recommended Find the need in the future to promote cooperation with international oil companies and oil service companies in all oil activities through cooperation and participation agreements and contracted to gain access to Iraq's strategic objectives for the purpose of providing new resources to finance the state budget as well as the need to take advantage of good global technical expertise and technology of modern provided by oil companies foreign operating in Iraq